2018
DOI: 10.1515/sjpain-2018-0120
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the antinociceptive effects of intrathecal DALDA peptides following bolus intrathecal delivery

Abstract: Abstract Background and aims We systematically characterized the potency and side effect profile of a series of small opioid peptides with high affinity for the mu opioid receptor. Methods Male Sprague Dawley rats were prepared with intrathecal (IT) catheters, assessed with hind pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…15 Conversely, PZM21, developed as a biased mu-opioid ligand, fails to activate MRGs and, as we show here, will not degranulate mast cells or produce a spinal mass. Alternatively, mu opioid ligands such as the dermorphin-derived peptides (DMT-DALDA) are extremely potent after intrathecal delivery, 16,17 and while they degranulate mast cells, we show here that the low concentrations required to produce mu opiate receptor mediated analgesia fails to produce a mass in vivo. 18,19…”
Section: Introductionmentioning
confidence: 75%
“…15 Conversely, PZM21, developed as a biased mu-opioid ligand, fails to activate MRGs and, as we show here, will not degranulate mast cells or produce a spinal mass. Alternatively, mu opioid ligands such as the dermorphin-derived peptides (DMT-DALDA) are extremely potent after intrathecal delivery, 16,17 and while they degranulate mast cells, we show here that the low concentrations required to produce mu opiate receptor mediated analgesia fails to produce a mass in vivo. 18,19…”
Section: Introductionmentioning
confidence: 75%
“…En este estudio los animales de experimentación se trataron con morfina intratecal durante cinco días antes de la administración de DMT-DALDA, y se observó que el efecto analgésico no se redujo como ocurre con la morfina como resultado del desarrollo de la tolerancia. Esta tolerancia asimétrica es interesante, ya que podría indicar que el péptido tiene un mejor efecto intrínseco en comparación con la morfina y abre una línea prometedora de investigación (16).…”
Section: Acción Analgésica Medularunclassified
“…In companion work we systematically examined the antinociceptive effects of the bolus delivery of a family of peptides built on the endogenous mu opioid peptide: dermorphin. In this allied work we observed that one of the analogues, DMT‐DALDA (H‐Dmt‐D‐Arg‐Phe‐Lys‐NH2), which displays a high affinity at the mu receptor (K i μ = 0.143 65 nM) and high receptor selectivity for mu vs. delta and kappa opioid receptors (K i δ /K i μ > 10,000 and K i κ /K i μ > 100) , and an extraordinary potency in blocking a spinal reflex (the tail‐flick) , hind paw withdrawal to a thermal stimulus and a reduction in formalin‐evoked flinching after bolus IT administration.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, several of these peptides carry a net positive charge at physiologic pH and are thus very hydrophilic, which suggests a long residency time in the intrathecal space, a property supporting an extended duration of action after intrathecal delivery. Indeed, following bolus delivery of equiactive doses, durations of action comparable to morphine were observed . To further characterize, the spinal actions of DMT‐DALDA and, for comparison, morphine, we undertook the following studies: 1) systematic time and concentration‐effect curves for chronically infused intrathecal DMT‐DALDA/morphine; 2) receptor pharmacology of spinally infused DMT‐DALDA/morphine using Nx (a pan‐opiate antagonist) and naltrindole (Ntd; a delta receptor preferring antagonist); and 3) examining the ability of DMT‐DALDa and morphine to produce mast cell degranulation, a mechanism proposed to mediate the opiate receptor independent generation of an intrathecal mass using the naltrexone‐insensitive, cutaneous flare observed after intradermal delivery .…”
Section: Introductionmentioning
confidence: 99%